Neutrophil elastase inhibitor (sivelestat) may be a promising therapeutic option for management of acute lung injury/acute respiratory distress syndrome or disseminated intravascular coagulation in COVID‐19. (28th August 2020) - Sahebnasagh, Adeleh; Saghafi, Fatemeh; Safdari, Mohammadreza; Khataminia, Masoud; Sadremomtaz, Afsaneh; Talaei, Zeinab; Rezai Ghaleno, Hassan; Bagheri, Mahdi; Habtemariam, Solomon; Avan, Razieh
Abstract: What is known and objective: This article summarizes the effects of sivelestat on acute lung injury/acute respiratory distress syndrome (ALI/ARDS) or ARDS with coagulopathy, both of which are frequently seen in patients with COVID‐19. Comment: COVID‐19 patients are more susceptible to thromboembolic events, including disseminated intravascular coagulation (DIC). Various studies have emphasized the role of neutrophil elastase (NE) in the development of DIC in patients with ARDS and sepsis. It has been shown that NE inhibition by sivelestat mitigates ALI through amelioration of injuries in alveolar epithelium and vascular endothelium, as well as reversing the neutrophil‐mediated increased vascular permeability. What is new and conclusions: Sivelestat, a selective NE inhibitor, has not been evaluated for its possible therapeutic effects against SARS‐CoV‐2 infection. Based on its promising beneficial effects in underlying complications of COVID‐19, sivelestat could be considered as a promising modality for better management of COVID‐19–induced ALI/ARDS or coagulopathy. Abstract : Neutrophil elastase (NE) contributes to inflammation by increasing vascular permeability and induction of pro‐inflammatory cytokines release, such as IL‐6 and IL‐8. Excessive activity of NE may lead to tissue damage and remodeling in several pulmonary diseases such as ALI/ARDS. Following the administration of sivelestat, the serum levels of TNF‐α, IL‐6, high mobility group box 1 (HMGB1), and NO were shown to decrease significantly. It could also substantially reduce the level of MCP‐1 mRNA in macrophages during ischemia‐reperfusion injury. Also, sivelestat improved DIC score in ARDS patients with DIC. Sivelestat could be considered as a promising treatment for better management of ALI/ARDS or coagulopathy in patients with COVID‐19.